Analisis Keterpengaruhan dan Kebaruan dalam Novel Yusuf Zulaikha Karya Nuruddin Abdurrahman Al-Jami dan Tafsir Surat Yusuf Karya Sayyid Quthb - Zahwa Amaly Fiddaraini; Muhammad Ariffur Rohman (Study Program of Arabic Language Teaching, 2021)
The title of this paper is “An Analysis of Influence and Novelty in Yusuf Zulaikha's Novel of the Work of Nuruddin Abdurrahman Al-Jami and Sayyid Quthb’s Tafsir of Surah Yusuf”. It used the comparative literature approach or literary application with analysis of illustration and novelty. The analysis is based on library research. This research used descriptive qualitative research. The result of this study is that there are elements of influence and also elements of novelty in both Jami's work and Quthb's work. The form of influence among them is an aspect of the principal ideas, some of the main characters, and the place settings, while the novelty element of Jami's work is more numerous than Quthb's work. The novelty elements contained in Jami's work are the names of figures, the place settings, and the language styles. The hypogram of both is Quran Surah Yusuf